2021
DOI: 10.3390/biology10050432
|View full text |Cite
|
Sign up to set email alerts
|

Identifying an lncRNA-Related ceRNA Network to Reveal Novel Targets for a Cutaneous Squamous Cell Carcinoma

Abstract: A cutaneous squamous cell carcinoma (cSCC) derived from keratinocytes is the second most common cause of non-melanoma skin cancer. The accumulation of the mutational burden of genes and cellular DNA damage caused by the risk factors (e.g., exposure to ultraviolet radiation) contribute to the aberrant proliferation of keratinocytes and the formation of a cSCC. A cSCC encompasses a spectrum of diseases that range from recursor actinic keratosis (AK) and squamous cell carcinoma (SCC) in situ (SCCIS) to invasive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…As an emerging class of regulatory RNAs, lncRNAs may participate in fundamental processes including cell cycle regulation, proliferation, apoptosis, self-renewal, metastasis and the DNA damage response through transcriptional or posttranscriptional regulation and thus give rise to diseases. Abnormally expressed lncRNAs play a key role in fibrosis [ 10 ] and different types of cancer, including breast cancer [ 11 – 13 ], lung cancer [ 14 , 15 ], colorectal cancer [ 16 , 17 ], esophageal squamous cell carcinoma [ 18 ], and cutaneous squamous cell carcinoma [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an emerging class of regulatory RNAs, lncRNAs may participate in fundamental processes including cell cycle regulation, proliferation, apoptosis, self-renewal, metastasis and the DNA damage response through transcriptional or posttranscriptional regulation and thus give rise to diseases. Abnormally expressed lncRNAs play a key role in fibrosis [ 10 ] and different types of cancer, including breast cancer [ 11 – 13 ], lung cancer [ 14 , 15 ], colorectal cancer [ 16 , 17 ], esophageal squamous cell carcinoma [ 18 ], and cutaneous squamous cell carcinoma [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs have been reported to be involved in various biological processes in tumors through multiple coordinative mechanisms, such as direct binding with DNA, RNA, and specific proteins [36]. The conventional view holds that lncRNAs primarily act as competitive endogenous RNAs (ceRNAs) to facilitate cSCC tumor progression by regulating miRNA-lncRNA interactions [37][38][39]. In contrast, accumulating evidence has indicated that lncRNAs, which are predominantly located in the cytoplasm, can exert their function by binding with targeted proteins and modulating the expression of corresponding proteins [40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…We used perl script to convert the probe IDs in the probe expression matrices to the corresponding gene symbols in the platform files 22 . Then, we used Limma package to analyze each obtained matrix file of gene symbols, calculated p values and |logFC|, and screen differential genes according to same criteria 23 . Our criteria for screening DEGs were P < 0.05 and an absolute value of logFC > 1.…”
Section: Methodsmentioning
confidence: 99%